Aggressive Giant Cell Reparative Granuloma of the Nasal Cavity. (27th March 2013) - Ishinaga, Hajime; Otsu, Kazuya; Mouri, Genshin; Takeuchi, Kazuhiko
Abstract : Giant cell reparative granuloma (GCRG) is an uncommon and nonneoplastic reactive tumor that involves the maxilla and mandible in the region of the head and neck. It is rare in the nasal cavity, and it might be misdiagnosed. We reported a very aggressive GCRG with intracranial invasion, which was treated surgically via a combined approach of a lateral rhinotomy with a craniotomy by bilateral coronal incision. The pathology was consistent with GCRG. A short literature review about diagnosis, clinical behavior, and treatment of this tumor entity is given.